Relasi Al-Qur’an Terhadap Tradisi Pernikahan Di Kalangan Kiai Kabupaten Pamekasan - jatim mistar; Abd.Kahar (STAI Al-Mujtama Pamekasan, 2023)
Abstract: Marriage is something sacred for the Pamekasan community, especially among the kiai. They are not arbitrary in choosing prospective wives or husbands for their children. There are many considerations made as an effort to find the best partner for their children. So that many of the kiai choose their sons and daughters also from the kiai, and this seems to have transformed into a tradition that is difficult to eliminate. So to answer questions about how the wedding tradition among the kiai of Pamekasan regency and the relationship of the Qur'an to the wedding tradition. So the research uses qualitative shorthand with descriptive data analysis method analysis-explanation. From the researcher's search of informants and existing documents (references). So the results of the study can be described as follows: marriage traditions among kiai Pamekasan regency by considering three things, namely (1) kafaah by prioritizing family, (2) kafaah by prioritizing social status, and (3) kafaah by prioritizing religion. However, based on existing reality, the concept of kafaah nasab or social which is the same in terms of nasab is still dominant among kiai today. The Qur'an does not contemplate kafaah nasab nor does it prohibit kafaah nasab. However, the Qur'an gives a strong message in marriage by emphasizing the importance of equality based on piety to Allah Almighty. al-Hujurat:13. Keywords: Tradition, Marriage, Kiai Pamekasan, Qur'an.